PENGARUH PEMBERIAN ZAKAT TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN MUARA DUA KOTA LHOKSEUMAWE - Nina Widyana; Munardi Munardi (JURNAL EKONOMIKA INDONESIA, 2019)
This study aims to analyze the effect of Zakat on Community Welfare in Muara Dua Subdistrict, Lhokseumawe City. This study uses primary data. The sample in this study is 28 respondents who are selected using Census sampling technique. The data analysis method used is a simple linear regression analysis and classical assumption tests. The results of the study partially show that Zakat has a positive and significant effect on the community welfare in Muara Dua Subdistrict, Lhokseumawe City.